The plausible association of MTHFR and ADORA2A polymorphisms with nodules in rheumatoid arthritis patients treated with methotrexate. Issue 2 (February 2017) - Soukup, Tomas; Dosedel, Martin; Nekvindova, Jana; Antonin Kubena, Ales; Tacheci, Ilja; Duintjer Tebbens, Jurjen; Vlcek, Jiri; Bradna, Petr; Barvik, Ivan; Pavek, Petr
Abstract : Objective: The treatment of rheumatoid arthritis (RA) patients with methotrexate (MTX) is linked to the development or progression of rheumatoid nodules. The aim of this study was to determine whether folate and adenosine pathways-related single nucleotide polymorphisms might be predictive of increased nodule formation in RA patients treated with oral MTX. Methods: A total of 185 Caucasian RA patients were enrolled in this cross-sectional study, all of whom fulfilled the 1987 RA criteria of the American College of Rheumatology; each patient had a history of MTX treatment. Results: A higher frequency of the MTHFR 1298AA genotype was found in 17 (70.8%) of 24 patients with general nodules [odds ratio (OR)=3.08, 95% confidence interval (CI): 1.20–7.69] and in 14 (73.7%) of 19 patients who developed nodules during MTX treatment (OR=3.55, 95% CI: 1.22–10.32). In contrast, a negative association with nodules during MTX treatment (OR=0.29, 95% CI: 0.08–1.10) was found for 19 (79.2%) patients with the TT genotype (rs2298383) in the adenosine A2a receptor gene ( ADORA2A ). However, the significance did not remain upon correction for multiple testing. The combination of MTHFR 1298AA along with ADORA2A rs2298383 CC or CT genotypes occurring in one-third of RA patients showed a higher frequency of general nodules 15/59 (25.4%) as well as developing nodules during MTX treatment 13/59 (22.0%) in comparison with the overall studied group: 24/185 (13.0%) and 19/185 (10.3%), respectively. Conclusion: This exploratory study indicates for the first time a plausible association of adenosine and folate pathways single nucleotide polymorphisms in nodules' etiopathogenesis.